PERAN LITERASI DIGITAL DALAM MENCEGAH DISINFORMASI PADA PESERTA DIDIK - Muhammad Hasan Basari; Radja Fatra Hilal; Rafliakmal; Muhammad ilham fadhilah (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
The rapid development of information technology provides students with easier access to various sources of knowledge. However, this situation also increases their exposure to disinformation, which can influence their understanding and decision-making. Digital literacy becomes an essential competency to help students identify, evaluate, and verify the information they encounter online. This study aims to examine the role of digital literacy in preventing disinformation among students by focusing on critical thinking skills, responsible media use, and the ability to assess information sources. Using a qualitative approach, the study emphasizes the importance of collaboration among schools, teachers, and families in guiding students through digital environments. The findings indicate that strengthening digital literacy significantly improves students’ ability to filter valid information, thus protecting them from the negative impact of disinformation and fostering more responsible learning habits